DUKUNGAN SUAMI TERHADAP KEJADIAN DROP OUT BAGI AKSEPTOR KELUARGA BERENCANA (KB) DI DESA DAN KOTA DI DAERAH ISTIMEWA YOGYAKARTA - Mufdlilah, Mufdlilah; Aryekti, Kanthi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
Family planning programs have a strategic, comprehensive and fundamental role in achieving a healthy and prosperous Indonesia. Efforts to deny pregnancy can be done by the use of contraceptives, but not all husbands agree to the use of contraceptives. What happens is drop outs of the acceptor. Women who are of productive and childbearing age, and the right to use contraceptives, as it is an important and necessary right. While it protects women’s health, contraceptives require the husband’s support to prevent dropouts and in selecting the proper contraceptive. Planned Parenthood service must be made through informed choice and consent of the couple, in order to avoid human rights violation, especially in the choice of contraceptives. The incidence of dropouts remains high for several reasons. This study was conducted to determine the role of husband support in incidents of dropouts in villages and the city. It is a descriptive research. The population in this study are acceptors drop out for 3 consecutive months, and are not pregnant. A sample of 100 people, and collection of data with a closed and open questionnaire, is presented descriptively. Husbands support the incidence of drop -out in the village and in the town due of the side effects at a rate of 38%, the husband does not support his wife KB 22 %, the other - the other 22 %, the husband does not receive contraceptive family planning in cities 82 % in rural 74 %, the husband asks stop KB in the city 48 % rural 60 %, the husband providing cost planning in the village 42 % in the city 34 %, the husband does not support the use of contraceptives in the city 38 % rural 38 %. In conclusion, increasing the support of her husband, improve mentoring and coaching acceptor drop out to be willing to use contraception again. Support includes acceptance of family planning services for the husband against wife in the city is higher than in the village.